新數位原生世代的素養導向學習及其能力發展 A Study of Competencies-Oriented Learning and Capabilities Development of the New Digital Native Generation - 王俊斌 Chun-Ping Wang (Higher Education Foundation, 2021)
本文先以二十一世紀新一波素養導向課程改革為脈絡，說明新數位科技發展 及其在跨域學習所帶來的進一步改變，進而以Prensky「數位原生世代」之分析基 礎，探究不同世代差異以及AI時代來臨之後「新數位原生世代」的變化。此外，筆者也將討論《2030年教育和技能的未來：OECD 2030年學習羅盤》提及的「未來導向能力」，透過當前新興數位化發展所造成的問題，藉由「能力取向」之觀點，提出以學習者能動性為核心的新興數位世代學習圖像。 This study takes the new wave of competencies-oriented curriculum reforms in the 21st century as context, explains the new digital technology development and its further changes on interdisciplinary learning, and explores generations' differences based on the analysis of Prensky's "digital native generation" to figure out "new digital naive generation" after the AI era. In addition, the author also discusses the seven futureoriented competencies of "Future of Education and Skills 2030: OECD Learning Compass 2030," and inquiries problems of current emerging digital development vias the "capabilities approach" to format an agency-based new digital native generation learning image.